2007
DOI: 10.1177/1077801207302699
|View full text |Cite
|
Sign up to set email alerts
|

The Factors Affecting Sexual Assaults Committed by Strangers and Acquaintances

Abstract: Research on the causes of sexual assault typically analyzes rape committed by acquaintances and strangers together, despite the fact that the characteristics of the assault in these two circumstances are very different. Thus, this work examines whether the causes of each type of sexual assault--stranger and acquaintance rape--differ. The results of the analyses reveal that variables that describe a culture of gender equality, prior child abuse, and prior sexual assaults are associated with acquaintance assault… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 46 publications
3
21
0
Order By: Relevance
“…Hyper-masculinity is associated with a higher involvement in violence, particularly sexual violence (Pazzani, 2007) and this trait has been documented in extractive industries across the globe. Carrington et al (2016) observed the link between a frontier masculinity and aggressive behavior in rural Australian mining towns.…”
Section: Workplace Culture That Supports Substance Abuse and Hyper-mamentioning
confidence: 99%
“…Hyper-masculinity is associated with a higher involvement in violence, particularly sexual violence (Pazzani, 2007) and this trait has been documented in extractive industries across the globe. Carrington et al (2016) observed the link between a frontier masculinity and aggressive behavior in rural Australian mining towns.…”
Section: Workplace Culture That Supports Substance Abuse and Hyper-mamentioning
confidence: 99%
“…Men sexually assault women in a wide range of contexts, and this has important implications for understanding the modus operandi of offenders (Pazzani, 2007). Notably, the context in which sexual abuse occurs (including the relationship between victim and offender) has a profound influence on the descriptions and information that women give about their assailants.…”
Section: Research Findings From Victim/survivors' Knowledgementioning
confidence: 99%
“…For example, in their interviews with convicted sexual offenders, Scully and Marolla (1993) identified a range of motivators, including the motivation to put women "in their place". A number of researchers have linked this idea of sexual conquest and control to a culture of attitudes towards sex and aggression that is embedded in masculinity (Cameron & Fraser, 1987;Scully & Marolla, 1993;Walklate, 2004) or "hypermasculinity" (Pazzani, 2007). In their study of stranger rapists, Greenall and West (2007) found that sexual desire and opportunism were motivating factors and that the offenders' behaviours could be categorised as either sexual or violent.…”
Section: Rewards Of Rape: Excitement and Powermentioning
confidence: 99%
“…Silverman, Kalick, Bowie, and Edbril (1988) applied a dichotomous approach to examine the differences between “blitz rapes” involving a sudden, surprise attack and “confidence rapes” where rapist and victim have had previous nonviolent interactions. The dichotomy parallels in large measure the common distinction between stranger- and acquaintance rapes (Pazzani, 2007).…”
Section: Previous Theoretical Arguments and Typologiesmentioning
confidence: 98%